It is the air that we breathe. Academic socialization as a key component for understanding how parents influence children's schooling - Unn-Doris K. Bæck (Taylor & Francis Group, 2017)
It is well known from the research literature that parents are important when it comes to determining individual school experiences, achievements and careers. However, in what way parental background influences education outcomes is less clear. In this article, the focus is on academic socialization as a specific aspect of parents' influence on children's school achievements. The main aims are to discuss the relationship between academic socialization and school performance and to discuss some implications of this relationship for the educational system's role as a producer and reproducer of social inequalities. Firstly, an understanding of the concept of academic socialization is presented. Secondly, implications of research findings pointing to the importance of academic socialization are critically assessed in terms of social inequalities in education. Thirdly, the educational system's presupposition for academic socialization is discussed in terms of inequity in education and symbolic violence.